Adsorptive Removal of a Pharmaceutical and Personal Care Product Oxybenzone from Water with Metal-Organic Frameworks - Tumpa, Naz Fathma; Jeong, Yeon-Koo (Asian Review of Environmental and Earth Sciences, 2018)
Oxybenzone, one of the most often detected pharmaceuticals and personal care products (PPCPS), from aqueous solutions and this PPCPs removal from water had been studied by using the highly porous metal-organic framework (MOF) ) MIL-101(Cr) and a modified MIL-101(Cr) called MIL-101-OH. Adsorption results showed that MIL-101-OH which contains functional group such as –OH, which was very effective for oxybenzone adsorption. The adsorption performance of MIL-101-OH over MIL-101-OH was found to be greater than that of MIL-101(Cr), which means the functionalization of primitive MOFs have a positive effect on adsorption. The kinetics of MIL-101-OH also showed higher result compare to MIL-101(Cr). So along with a high adsorption capacity and repaid adsorption which is important for commercial applications.